The fixer - Finder, Joseph (Dutton/Penguin Random House, 2015)
"New York Times bestselling author Joseph Finder delivers his next breakneck stand-alone thriller, following 2014's bestseller Suspicion. When Rick Hoffman loses his job and apartment, his only option is to move back into--and renovate--the home of his miserable youth, now empty and in decay since his father's stroke. But when he starts to pull it apart, he makes an electrifying discovery that will put his life in peril--and change everything he thought he knew about his father. "--